Evolution of the S-Genomes in Triticum-Aegilops Alliance: Evidences From Chromosome Analysis - Ruban, Alevtina S.; Badaeva, Ekaterina D. (Frontiers in Plant Science, 2018)
Five diploid Aegilops species of the Sitopsis section: Ae. speltoides, Ae. longissima, Ae. sharonensis, Ae. searsii, and Ae. bicornis, two tetraploid species Ae. peregrina (=Ae. variabilis) and Ae. kotschyi (Aegilops section) and hexaploid Ae. vavilovii (Vertebrata section) carry the S-genomes. The B- and G-genomes of polyploid wheat are also the derivatives of the S-genome. Evolution of the S-genome species was studied using Giemsa C-banding and fluorescence in situ hybridization (FISH) with DNA probes representing 5S (pTa794) and 18S-5.8S-26S (pTa71) rDNAs as well as nine tandem repeats: pSc119.2, pAesp_SAT86, Spelt-1, Spelt-52, pAs1, pTa-535, and pTa-s53. To correlate the C-banding and FISH patterns we used the microsatellites (CTT)10 and (GTT)9, which are major components of the C-banding positive heterochromatin in wheat. According to the results obtained, diploid species split into two groups corresponding to Emarginata and Truncata sub-sections, which differ in the C-banding patterns, distribution of rDNA and other repeats. The B- and G-genomes of polyploid wheat are most closely related to the S-genome of Ae. speltoides. The genomes of allopolyploid heat have been evolved as a result of different species-specific chromosome translocations, sequence amplification, elimination and re-patterning of repetitive DNA sequences. These events occurred independently in different wheat species and in Ae. speltoides. The 5S rDNA locus of chromosome 1S was probably lost in ancient Ae. speltoides prior to formation of Timopheevii wheat, but after the emergence of ancient emmer. Evolution of Emarginata species was associated with an increase of C-banding and (CTT)10-positive heterochromatin, amplification of Spelt-52, re-pattering of the pAesp_SAT86, and a gradual decrease in the amount of the D-genome-specific repeats pAs1, pTa-535, and pTa-s53. The emergence of Ae. variabilis and Ae. kotschyi did not lead to significant changes of the S*-genomes. However, partial elimination of 45S rDNA repeats from 5S* and 6S* chromosomes and alterations of C-banding and FISH-patterns have been detected. Similarity of the Sv-genome of Ae. vavilovii with the Ss genome of diploid Ae. searsii confirmed the origin of this hexaploid. A model of the S-genome evolution is suggested.